Gender Responsive Budgeting (Grb): A Study Of Policy Internalisation And Its Implementation Among The Policy Actors In Malaysia - Mohd Karim, Anis Farahwahida (2024)
It is a preliminary study conducted to examine the status of GRB implementation in Malaysia. Besides, it is to investigate how policy actors’ understand the GRB and internalise it in the current Outcome-Based Budgeting (OBB) format. Throughout the study, several real challenges were identified that hinder the complete implementation of the policy.